Understanding the role of gamification and loyalty programs in restaurant apps: a systematic literature review and conceptual framework development - Sutrisno, Julius; Tarigan, Aritha; Purnomo, Ivanna Dominique Celesta (Universitas Bunda Mulia, 2026)
The rapid digital transformation in the restaurant industry has led to the widespread adoption of mobile applications incorporating gamification, rewards, and loyalty programs to enhance customer engagement and retention. This study conducts a systematic literature review to synthesize recent research on these strategies in restaurant mobile apps. Following the PRISMA guidelines, a comprehensive search of the Scopus database identified 587 records, with 42 studies published between 2020 and 2026 meeting the inclusion criteria. Thematic analysis revealed four primary themes: (1) mechanisms of user engagement driven by motivational affordances fulfilling autonomy, competence, and relatedness needs; (2) architecture of rewards and loyalty programs evolving from transactional to digital, tiered, and personalized ecosystems; (3) outcomes on customer loyalty encompassing both attitudinal and behavioral dimensions; and (4) challenges including privacy concerns, poor design, and wellbeing implications. The findings are interpreted through Self-Determination Theory, Service-Dominant Logic, and Oliver's loyalty framework, demonstrating that gamification enhances customer experience and fosters loyalty through need satisfaction and value co-creation. Practical implications guide restaurant managers and app developers in designing layered gamification experiences, navigating personalization-privacy trade-offs, and implementing ethical engagement practices. The review identifies critical research gaps, including the need for longitudinal studies, cross-cultural comparisons, and investigations of negative outcomes. This synthesis contributes to theoretical development in digital loyalty and offers actionable insights for industry practitioners.